A Major Gene for Bovine Ovulation Rate - Kirkpatrick, Brian W. (PLoS One, 2015)
Half-sib daughters sired by a bull believed to be a carrier of a major gene for high ovulation rate were evaluated for ovulation rate and genotyped in an effort to both test the hypothesis of segregation of a major gene and to map the gene’s location. A total of 131 daughters were produced over four consecutive years at a University of Wisconsin-Madison research farm. All were evaluated for ovulation rate over an average of four estrous cycles using transrectal ultrasonography. The sire and all daughters were genotyped using a 3K SNP chip and the genotype and phenotype data were used in a linkage analysis. Subsequently, daughters recombinant within the QTL region and the sire were genotyped successively with 50K and 777K SNP chips to refine the location of the causative polymorphism. Positional candidate genes within the fine-mapped region were examined for polymorphism by Sanger sequencing of PCR amplicons encompassing coding and 5’ and 3’ flanking regions of the genes. Sire DNA was used as template in the PCR reactions. Strong evidence of a major gene for ovulation rate was observed (p<1x10(-28)) with the gene localized to bovine chromosome 10. Fine-mapping subsequently reduced the location to a 1.2 Mb region between 13.6 and 14.8 Mb on chromosome 10. The location identified does not correspond to that for any previously identified major gene for ovulation rate. This region contains three candidate genes, SMAD3, SMAD6 and IQCH. While candidate gene screening failed to identify the causative polymorphism, three polymorphisms were identified that can be used as a haplotype to track inheritance of the high ovulation rate allele in descendants of the carrier sire.